An efficient and scalable synthesis of 2, 4-di-N-acetyl-l-altrose (l-2, 4-Alt-diNAc). Issue 19 (19th March 2021) - Niedzwiecka, Anna; Sequeira, Carita; Zhang, Ping; Ling, Chang-Chun
Abstract : An efficient and scalable synthesis of pseudaminic acid precursor l -2, 4-Alt-diNAc was developed from l -fucose. The desired l -altro configuration and N -acetamido substitutions ensued from a sequence of highly regio- and stereoselective transformations. Abstract : Bacterial nonulosonic acids such as pseudaminic acids and others constitute a family of 9-carbon monosaccharides that contain a common 3-deoxy-2-ketoacid fragment but differ in their stereochemistries at 5 stereogenic centers between C-4 to C-8. Their unique structures make them attractive targets for use as antigens in vaccinations to combat drug-resistant bacterial infections and their challenging stereochemistries have attracted considerable attention from chemists. In this work we report the development of an improved synthesis for 2, 4-di- N -acetyl-l -altrose (l -2, 4-Alt-diNAc), which is a key hexose required for the chemical and chemoenzymatic synthesis of pseudaminic acids. Using l -fucose as a starting material, our synthesis overcomes several pitfalls in previously reported syntheses.